DIAGNOSIS OF ATOPIC DERMATITIS IN CHILDREN - Khodjayeva , Shakhzoda (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
Atopic dermatitis is a common chronic allergic disease in children, and its early diagnosis is important in preventing severe disease and relapses. To assess the effectiveness of clinical, laboratory and allergological diagnostic methods for atopic dermatitis in children.